Emerging Concepts in Innate Lymphoid Cells, Memory, and Reproduction - Favaro, Rodolfo R.; Phillips, Katherine; Delaunay-Danguy, Romane; Ujčič, Kaja; Markert, Udo R. (Frontiers in Immunology, 2022)
Members of the innate immune system, innate lymphoid cells (ILCs) encompass five major populations (Natural Killer (NK) cells, ILC1s, ILC2s, ILC3s, and lymphoid tissue inducer cells) whose functions include defense against pathogens, surveillance of tumorigenesis, and regulation of tissue homeostasis and remodeling. ILCs are present in the uterine environment of humans and mice and are dynamically regulated during the reproductive cycle and pregnancy. These cells have been repurposed to support pregnancy promoting maternal immune tolerance and placental development. To accomplish their tasks, immune cells employ several cellular and molecular mechanisms. They have the capacity to remember a previously encountered antigen and mount a more effective response to succeeding events. Memory responses are not an exclusive feature of the adaptive immune system, but also occur in innate immune cells. Innate immune memory has already been demonstrated in monocytes/macrophages, neutrophils, dendritic cells, and ILCs. A population of decidual NK cells characterized by elevated expression of NKG2C and LILRB1 as well as a distinctive transcriptional and epigenetic profile was found to expand during subsequent pregnancies in humans. These cells secrete high amounts of interferon- and vascular endothelial growth factor likely favoring placentation. Similarly, uterine ILC1s in mice upregulate CXCR6 and expand in second pregnancies. These data provide evidence on the development of immunological memory of pregnancy. In this article, the characteristics, functions, and localization of ILCs are reviewed, emphasizing available data on the uterine environment. Following, the concept of innate immune memory and its mechanisms, which include epigenetic changes and metabolic rewiring, are presented. Finally, the emerging role of innate immune memory on reproduction is discussed. Advances in the comprehension of ILC functions and innate immune memory may contribute to uncovering the immunological mechanisms underlying female fertility/infertility, placental development, and distinct outcomes in second pregnancies related to higher birth weight and lower incidence of complications.